Specific Features of Nouns in French and Uzbek Languages (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
A noun is an independent part of speech that denotes an object, person or phenomenon and answers the questions “who?” “what?” or “where?”. A noun is an important word class in any language, including Uzbek and French. This article discusses the specific features of nouns in Uzbek and French.